ISPD Overexpression Enhances Ribitol-Induced Glycosylation of α-Dystroglycan in Dystrophic FKRP Mutant Mice - Cataldi, Marcela P. (Mol Ther Methods Clin Dev, 2019)
Dystroglycanopathy, a subgroup of muscular dystrophies, is characterized by hypoglycosylation of α-dystroglycan (α-DG), which reduces its laminin-binding activity to extracellular matrix proteins, causing progressive loss of muscle integrity and function. Mutations in the fukutin-related protein (FKRP) gene are the most common causes of dystroglycanopathy. FKRP transfers ribitol-5-phosphate to the O-mannosyl glycan on α-DG from substrate cytidine diphosphate (CDP)-ribitol, which is synthesized by isoprenoid synthase domain-containing protein (ISPD). We previously reported that oral administration of ribitol restores therapeutic levels of functional glycosylation of α-DG (F-α-DG) in a FKRP mutant mouse model. Here we examine the contribution of adeno-associated virus (AAV)-mediated overexpression of ISPD to the levels of CDP-ribitol and F-α-DG with and without ribitol supplementation in the disease model. ISPD overexpression alone and in combination with ribitol improves dystrophic phenotype. Furthermore, the combined approach of ribitol and ISPD acts synergistically, increasing F-α-DG up to 40% of normal levels in cardiac muscle and more than 20% in limb and diaphragm. The results suggest that low levels of substrate limit production of CDP-ribitol, and endogenous ISPD also becomes a limiting factor in the presence of a supraphysiological concentration of ribitol. Our data support further investigation of the regulatory pathway for enhancing efficacy of ribitol supplement to FKRP-related dystroglycanopathy.